Batrachospermum qujingense (Batrachospermales, Rhodophyta), a new freshwater red algal species from Southwest China - Fang, Kun-Peng; Nan, Fang-Ru; Feng, Jia; Lv, Jun-Ping; Liu, Qi; Liu, Xu-Dong; Xie, Shu-Lian (Phytotaxa, 2020)
Batrachospermum is a widely distributed genus in China. Nonetheless, many taxa recorded previously have no molecular data. In this study, a new species of Batrachospermum called Batrachospermum qujingense is described and illustrated from Qujing, Yunnan, Southwest China, based on morphological observations and a phylogenetic analysis. This species is distinguished morphologically from other species by dioecious thalli, straight carpogonial branches with 7–9 cells and stalked angled obovoid or inflated-clavate trichogynes. In addition, a phylogenetic analysis of the molecular data from the rbcL, COI-5P, and psbA genes indicated separation between the new species proposed in this study and other species in the genus Batrachospermum (4.0–5.3% for rbcL, 7.7%–10.6% for COI-5P, and 2.2–3.2% for psbA ). This is the first species of Batrachospermum reported in Yunnan and the third species of Batrachospermum with molecular data in China. The description of the new species and geographical distribution expands the diversity of freshwater red algae in China.